Digital Assets and Islamic Inheritance Law: Reinterpreting the Concept of Māl through Maqāṣid Sharī‛ah - Bunga Desyana Pratami; Yos Johan Utama; Ana Silviana; Imaro Sidqi; Iqbal Kamalludin (Universitas Islam Sultan Agung, 2026)
Purpose - The rapid development of the digital economy has engendered new forms of wealth that challenge classical concepts of ownership within Islamic law, particularly in the context of inheritance law. Digital assets—such as cryptocurrency, non-fungible tokens (NFTs), and economically valuable digital accounts—present significant legal questions regarding their status as inheritable property, especially given their intangible nature and reliance on technological systems. In practice, many digital assets become inaccessible following the owner's death, often due to the loss of passwords or private keys. This situation creates a disparity between classical legal doctrines and contemporary realities. This study aims to analyse the legal status of digital assets within Islamic inheritance law through a reinterpretation of the concept of wealth (māl) employing an objective of the Islamic law (maqāṣid al-sharīʿah) approach.Methodology/approach - This research employs a normative juridical methodology, utilising both conceptual and maqāṣid-based approaches. It is conducted through a comprehensive literature review of classical Islamic jurisprudence (fiqh) texts and maqāṣid theory, supplemented by an analysis of contemporary practices concerning digital asset.Findings - Although some classical scholars—particularly within the Ḥanafī school—emphasised the material aspect of māl, the majority of scholars recognise lawful economic value and benefit (manfaʿah mubāḥah) as the primary criteria for determining property status. From this perspective, digital assets qualify as māl because they possess economic value, can be owned, and are transferable. Furthermore, the framework of maqāṣid al-sharīʿah, particularly the principles of protection of wealth (ḥifẓ al-māl) and protection of lineage (ḥifẓ al-nasl), provides a robust normative basis for recognising digital assets as inheritable property. Therefore, the reinterpretation of māl through a maqāṣid approach facilitates the integration of digital assets into Islamic inheritance law in both a normative and contextual manner.Conclusion - This study concludes by advocating the establishment of legal and technical mechanisms designed to protect the rights of heirs in the digital age, thereby minimising the disparity between doctrinal principles and practical application.